Optimizing Google My Business to Increase the Competitiveness of Mainan Village MSMEs in Thematic Community Service Activities Universitas Indo Global Mandiri - Sabina, Veni Allya; Sukesih, Ade Ayu; Deninta, Dinda Dwi; Alie, Juhaini; Munandar, Aris; Ghina, Aliah (Manunggal Halim Jaya, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economy, yet they still face challenges in digitalization. The Thematic Community Service Program (KKNT) in Mainan Village, Sembawa District, Banyuasin Regency, aimed to enhance the digital capacity of MSMEs through the use of Google My Business (GMB). The methods used included observation, seminars, training, and evaluation. The results showed that MSMEs were able to create and manage Google My Business (GMB) accounts independently. A case study of the Rengginang Ceu Eem business demonstrated that the business profile was successfully displayed on Google Search and Google Maps with complete information, including the business name, category, address, operating hours, and telephone number. The use of Google My Business (GMB) has been proven to increase business visibility, expand marketing reach, and strengthen consumer trust. This activity significantly contributes to encouraging the digital transformation of MSMEs in villages to be more adaptive to modern market competition.